Gender Relations during Pandemic Era in Indonesia: Negotiation and Resistance of Urban Woman Workers at Work from Home (WFH) in Family - Radius Setiyawan; Arin Setiyowati; Maulida Maulida (Sawwa: Jurnal Studi Gender, 2022)
After the COVID-19 pandemic, a new condition (New Normal) affects a variety of human activities, especially the working conditions of urban women. Until now, women have been more than viewed as merely objects of domestication, worker exploitation, verbal or physical violence, and other forms of discrimination. This study aims to disclose an alternative perspective on women as subjects actively negotiating their domestic and public roles. This new condition introduces adjustments to women's work-at-home (work-from-home) and family responsibilities during the pandemic (approximately for two years). This research used a qualitative method with in-depth interviews through mapping a new condition of women who were able to negotiate and resist during the pandemic in their families. This study was conducted with working mothers in Surabaya, Sidoarjo, and Gresik. The findings of this study revealed that urban working women frequently negotiate and resist their roles, meaning that gender roles or relations are not static but are always in the process of being.